Seroprevalence of SARS-CoV-2 Among Frontline Healthcare Personnel During the First Month of Caring for Patients With COVID-19—Nashville, Tennessee. (6th June 2020) - Stubblefield, William B; Talbot, H Keipp; Feldstein, Leora R; Tenforde, Mark W; Ur Rasheed, Mohammed Ata; Mills, Lisa; Lester, Sandra N; Freeman, Brandi; Thornburg, Natalie J; Jones, Ian D; Ward, Michael J; Lindsell, Christopher J; et al.
Abstract: Among 249 healthcare personnel who worked in hospital units with COVID-19 patients for 1 month, 19 (7.6%) tested positive for SARS-CoV-2 antibodies. Only 11 (57.9%) of the 19 personnel with positive serology reported symptoms of a prior illness, suggesting asymptomatic healthcare personnel could be an important source of SARS-CoV-2 transmission.